Oxygen and aluminum diffusion in α-Al2O3: How much do we really understand? - Heuer, A.H. (Journal of the European Ceramic Society, 2008)
Research activities relating to oxygen and aluminium diffusion in doped and undoped alpha-alumina, both polycrystalline and single crystal, are reviewed. Issues discussed include aluminium lattice diffusion, and oxygen lattice and grain boundary diffusion, including enhanced grain boundary diffusion and pipe diffusion. Also discussed is diffusion of creep in polycrystalline alumina and the oxidation of Al2O3-scale-forming alloys. 61 refs.